2013
DOI: 10.1371/journal.pone.0075895
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Trans Interactions in Yeast Chromosomes

Abstract: Three-dimensional organization of the genome is important for regulation of gene expression and maintenance of genomic stability. It also defines, and is defined by, contacts between different chromosomal loci. Interactions between loci positioned on different chromosomes, i.e. “trans” interactions are one type of such contacts. Here, we describe a case of inducible trans interaction in chromosomes of the budding yeast S. cerevisiae. Special DNA sequences, inserted in two ectopic chromosomal loci positioned in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 75 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…3A and Methods). We also carried out the same measurement by using two cis segments 13 kb apart on ChrXV as a positive control (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A and Methods). We also carried out the same measurement by using two cis segments 13 kb apart on ChrXV as a positive control (22).…”
Section: Resultsmentioning
confidence: 99%
“…According to a statistical analysis of the Hi-C data, the Gal4 binding sites (GAL1 activator) cluster in the nucleus (21). β-estradiol-induced GAL1pr on two different chromosomes could form trans interactions under the activating condition in haploid yeast (22). The upstream activation sequence (UAS) of GAL1pr was able to activate transcription in trans when introduced into the Drosophila genome (23).…”
mentioning
confidence: 99%
“…The studies so far all use the classic activation system, GAL1 promoter, as the model. It was first found that β-estradiol-induced GAL1 promoters at allelic locations could form significantly stronger transinteractions under the activating condition (Mirkin et al 2013), suggesting that this interaction is intricately related to gene expression. Extending from this observation, Zhang et al showed that two allelic reporters, one driven by wild-type GAL1 promoter and the other by a mutated GAL1 promoter with delayed response to galactose induction, physically associate upon induction.…”
mentioning
confidence: 99%
“…First, co-regulated genes can interact with each other, but only when they are located in certain genomic loci. For example, among the insertion sites tested, GAL1 reporters only interact when they are at allelic locations, or on non-homologous chromosomes but have equal distance to centromere (Mirkin et al 2013; Zhang and Bai 2016). Similarly, only a small fraction of Met4-targeted genes seems to cluster, and the MET3 reporter makes contacts with the cluster only when inserted into certain loci (Du et al 2017).…”
mentioning
confidence: 99%
“…3C assay was done exactly as in 39 . For each 3C template, the intensity of signal PCR product was normalized to the intensity of normalization PCR product and averaged among the triplicates.…”
Section: Methodsmentioning
confidence: 99%